1990
DOI: 10.1038/bjc.1990.92
|View full text |Cite
|
Sign up to set email alerts
|

The potential of carboxypeptidase G2: antibody conjugates as anti-tumour agents. II. In vivo localising and clearance properties in a choriocarcinoma model

Abstract: Summary The in vivo localising and clearance properties of conjugates of the folate-degrading enzyme carboxypeptidase G2 (CPG2) with anti-human chorionic gonadotrophin (W14A) were measured in nude mice bearing CC3 choriocarcinoma xenografts. Conjugates of W14A-F (ab')2 fragment coupled to CPG2 localised in tumour as effectively as native antibody alone but showed lower uptake in other major tissues. The clearance rates of conjugates prepared with intact antibody or F (ab')2 fragment were shown to be up to five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…However, this system was only active against xenografts producing human chorionic gonadotrophin, the Ag recognized by W14 [15]. Interestingly, secretion of the Ag from the tumor aided clearance of the conjugate from circulation [16].…”
Section: Carboxypeptidase G (Cpg)mentioning
confidence: 98%
“…However, this system was only active against xenografts producing human chorionic gonadotrophin, the Ag recognized by W14 [15]. Interestingly, secretion of the Ag from the tumor aided clearance of the conjugate from circulation [16].…”
Section: Carboxypeptidase G (Cpg)mentioning
confidence: 98%
“…CONCLUSION Macromolecular drugs have shown superiority in a number of therapeutic applications, most notably in oncology. The use of antibodies for targeted cancer therapy has shown considerable preclinical promises (103,104) and many different systems are currently undergoing thorough clinical evaluation (105,106). As discussed earlier, synthetic macromolecules have achieved particular success in abrogating the immunogenicity of a variety of therapeutic molecules, including many different allogenic enzymes, and adding biological response modifying effects as described briefly.…”
Section: Polymer-conjugated Anticancer Agentsmentioning
confidence: 99%
“…The immune response is a potential impediment to the repeated or sustained systemic use of any exogenous protein or other macromolecule in humans. Clinical and preclinical therapy studies have shown that exogenous proteins can be effective in vivo as artificial receptors for the capture of radionuclides (Goodwin et al 1986; Axworthy et al 2000), as toxins (Wawrzynczak 1991) or as catalysts for the activation of prodrugs (Melton et al 1990; Senter 1990; Meyer et al 1993 ). In some cases a human protein can carry out these functions, but frequently human proteins are unavailable or inadequate, or non‐human proteins are preferable.…”
mentioning
confidence: 99%